Cinematizing the Victorian Novel to Cinema "Pride and Prejudice" - Rahmah, Nurul Aulia; Iman, Diah Tyahaya (Vivid: Journal of Language and Literature, 2022)
Jane Austen's novels and clever heroines and romantic interests have been adapted into movies and television shows for decades. This study explores a literary adaptation of Jane Austen's novel entitled Pride and Prejudice, published in1813. It was adapted to the screen by Joe Wright in 2005 and written by Deborah Moggach. We shall discuss how Joe Wright interpreted the setting and conflict. This research was conducted using the adaptation theory proposed by Linda Hutcheon. We argue that the movie interestingly altered the setting to show the characters' romantic scenes and the major characters' social economy level. The movie provides its audience transposition of major external and internal conflicts among the major characters. The movie has minimized the issues of social condition status and women's roles in the Victorian era. Moreover, the film focuses on finding true love, the power of love, and the romantic scene. Joe Wright realistically maintains the struggle of romantic relationship between Darcy and Elizabeth and the beautiful landscape setting makes the audience feel it.